A Case of Multiple Phleboliths on the Medial Side of the Right Mandible - Shinichi Sato; Masato Takahashi; Tetsu Takahashi (Case Reports in Dentistry)
A 66-year-old female patient was admitted to the orthopedic department due to a left femoral neck fracture. She received perioperative oral management prior to femoral head replacement. Laboratory blood tests indicated an elevated D-dimer level, which suggested the presence of a venous malformation. Computed tomography, magnetic resonance imaging, and short TI inversion recovery indicated the presence of multiple phleboliths medial to the right mandibular ramus. No swelling, redness, or salivary colic pain was observed. Owing to the absence of clinical symptoms, the patient elected to undergo observation of the lesion, as opposed to surgical treatment.